The The Influence of Motivation, Work Discipline and Work Environment on Employee Performance Through Job Satisfaction as an Intervening Variable at (PT.XYZ) Jakarta - Rachman, Nuriza; Saluy, Ahmad Badawi (Dinasti International Journal of Digital Business Management, 2024)
This research aims to test and analyze the influence of motivation, work discipline and work environment on employee performance through job satisfaction as an intervening variable at PT. XYZ (Jakarta). The population of this research is employees of PT. XYZ (Jakarta) with a total sample of 140 employees with an observation period of 2023. This research is a quantitative research using the data analysis method using structural equation models-partial Least Square (SEM-PLS). The research results found that motivation, work discipline and the work environment have a positive and significant effect on performance, motivation, work discipline and the work environment have a positive and significant effect on job satisfaction, motivation, work discipline and the work environment have a positive and significant effect on performance through job satisfaction